Implementation of Physical Education Curriculum in Athletics Learning for Sprint Running at Junior High School - Akhmad Sobarna; Sumbara Hambali; Sony Hasmarita; Mohd Shariman Shafie (Pedagogy Review, 2026)
The effective implementation of Physical Education (PE) curricula in athletics instruction remains a persistent challenge at the secondary school level, particularly regarding teachers' pedagogical competence and the contextual adaptation of curricula. This study aims to examine the implementation of the PE curriculum in sprint running instruction among eighth-grade students at the Junior High School level. A descriptive quantitative design with a survey approach was employed, involving 94 eighth-grade students selected through total sampling. Data were collected using a validated curriculum implementation observation sheet (validity: r = 0.87; reliability: α = 0.88), a 60-meter sprint performance test, and a learning motivation questionnaire. Data were analyzed using descriptive statistics, paired-samples t-test, and N-gain score calculation. PE curriculum implementation was categorized as "fairly good," with a mean score of 71.4 (SD = 8.32). Sprint running performance improved significantly from pre-test (M = 9.84 s) to post-test (M = 9.21 s), t(93) = 8.74, p 0.001, yielding a moderate N-gain score of 0.42. Multiple regression analysis identified teacher pedagogical competence, lesson plan quality, availability of facilities, and student learning motivation as significant predictors of curriculum implementation effectiveness, collectively accounting for 68% of the variance. These findings demonstrate that while overall curriculum implementation remains at a moderate level, it was sufficient to produce meaningful and statistically significant gains in student sprint performance, with teacher competence and instructional planning quality emerging as central determinants. Sustained improvement requires continuous professional development for PE teachers and the adoption of contextually adapted instructional modules responsive to students' learning needs. Keywords:  Physical education, athletics learning, junior high school, quantitative  research.